Primary diagnosis and emergency treatment - Castiglioni Barriere, Juan C; Bergalli, Luis E (Cirugía del Uruguay, 1974)
Patients with neck wounds and presenting symptoms of shock or acute respiratory insufficiency may die within a short period in such problems are not corrected. Primary diagnosis and emergency treatment prior to surgery are fundamental. Acute respiratory insufficiency is due to engagement of high airway or to hypertensive pleural occupation. The paper contains a description pf main obstruction mechanisms, lesion and compression of airway and principies of therapy, with special attention to the peculiarities of emergency tracheostomy. There is possibility of hypertensive pneumothorax which should be immediately diagnosed and treated. In cases of air obstruction and pleural occupation -.vhich are toller a ble to the patient, the period of anesthesic induction is critical Shock is the equivalent to severe hemorrhage, either exterior or into the pleural cavity. Heart plugging is possible. There are severa! manouvres for achieving temporary pre-operatory hemostasis and details regarding reinstatement of volemia. Finally, the seriousness of neck wounds associated t::l lesions in other parts of the body renders necessary simultaneous approach by two teams of surgeous.